(untitled) (London Journal of Research In Management & Business, 2024)
In this article, the author tries to make an overview of Russia electricity market from market from its appearance until today. The electricity market legislation and the authorities which assure market regulation are identified and presented. Transport and distribution system is overview and their connection.